2012
DOI: 10.1093/cid/cir988
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Transmitted Drug-Resistant HIV Among Young Pregnant Women in Ouagadougou, Burkina Faso

Abstract: Burkina Faso began rapid antiretroviral therapy (ART) scale-up in 2003 and by December 2009, 26,448 individuals were on treatment. With rapid scale-up of ART, some degree of human immunodeficiency virus transmitted drug resistance (TDR) is inevitable. Following World Health Organization methods, between June 2008 and July 2009, Burkina Faso assessed TDR in primigravid pregnant women aged <25 years attending antenatal care clinics in Ouagadougou, Burkina Faso. TDR was classified as moderate (5%-15%) for both nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(12 reference statements)
0
6
0
1
Order By: Relevance
“…Therefore, resistance mutation to NRTIs is the most frequent form of drug resistance, as found in previous studies. Recent studies those conducted in sub‐Saharan Africa had reported a higher trend of primary HIV‐1 drug resistance [Hamers et al, 2011; Hunt et al, 2012; Sigaloff et al, 2012; Somda et al, 2012]. For PI‐associated mutations, the rate of resistance observed was lower than in previous reports from resource‐rich areas.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, resistance mutation to NRTIs is the most frequent form of drug resistance, as found in previous studies. Recent studies those conducted in sub‐Saharan Africa had reported a higher trend of primary HIV‐1 drug resistance [Hamers et al, 2011; Hunt et al, 2012; Sigaloff et al, 2012; Somda et al, 2012]. For PI‐associated mutations, the rate of resistance observed was lower than in previous reports from resource‐rich areas.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies in West Africa have found low levels of pretreatment DR in Guinea, moderate levels in Mali and levels varying from low to moderate in Cape Verde [ 39 43 ]. Levels of pretreatment DR in pregnant women were low in studies from Ghana and Nigeria, while moderate levels were observed in Burkina Faso [ 44 – 46 ]. Our study, which was performed twelve years after ART roll out in Guinea Bissau, found levels of pretreatment DR higher than the above mentioned studies, a difference that may be associated with the time of the studies after national ART scale up in the countries [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, resistance mutation to NRTIs is the most frequent form of drug resistance, as found in previous studies. Recent studies those conducted in sub-Saharan Africa had reported a higher trend of primary HIV-1 drug resistance [Hamers et al, 2011;Hunt et al, 2012;Sigaloff et al, 2012;Somda et al, 2012]. For PI-associated mutations, the rate of resistance observed was lower than in previous reports from resource-rich areas.…”
Section: Discussionmentioning
confidence: 60%